State variation in retail promotions and advertising for Marlboro cigarettes. Issue 4 (1st December 2001) - Slater, Sandy; Chaloupka, Frank J; Wakefield, Melanie
Abstract : BACKGROUND: There is some evidence that tobacco companies marketing efforts undermine the effects of comprehensive tobacco control programmes. OBJECTIVE: To determine whether point-of-purchase advertising and promotions are more pervasive in states where comprehensive tobacco control programmes are underway. DESIGN: Cross sectional survey using 1996 data, with merged records of the existence of local tobacco advertising restrictions. PARTICIPANTS AND SETTING: 581 tobacco retail stores located in close proximity to high schools in mainland USA. MAIN OUTCOME MEASURES: Existence of gift-with-purchase, number of interior advertisements, and exterior store advertisements for Marlboro cigarettes. RESULTS: After controlling for store type and existence of advertising restrictions, offer of a gift-with-purchase for Marlboro cigarettes was significantly more likely in states with comprehensive tobacco control programmes than those without programmes (odds ratio 2.59, 95% confidence interval 1.57 to 4.26). Although not significant, results show an increase in the number of interior and exterior store advertisements for stores located in states with a comprehensive tobacco control programme than those in other states. CONCLUSION: Results suggest some point-of-purchase tobacco promotions and advertising are more pervasive in states with comprehensive tobacco control programmes. These efforts are likely to act against the objectives of programmes and need to be accounted for in programme evaluations.